Pulmonary Oxygen Toxicity in Navy Divers: A Crossover Study Using Exhaled Breath Analysis After a One-Hour Air or Oxygen Dive at Nine Meters of Sea Water - Wingelaar, Thijs T.; van Ooij, Pieter-Jan A. M.; Brinkman, Paul; van Hulst, Rob A. (Frontiers in Physiology, 2019)
Introduction:Exposure to hyperbaric hyperoxic conditions can lead to pulmonary oxygen toxicity. Although a decrease in vital capacity has long been the gold standard, newer diagnostic modalities may be more accurate. In pulmonary medicine, much research has focussed on volatile organic compounds (VOCs) associated with inflammation in exhaled breath. In previous small studies after hyperbaric hyperoxic exposure several methyl alkanes were identified. This study aims to identify which VOCs mark the development of pulmonary oxygen toxicity. Methods:In this randomized crossover study, twelve divers of the Royal Netherlands Navy made two dives of one hour to 192.5 kPa (comparable to a depth of 9 meters of sea water) either with 100% oxygen or compressed air. At 30 min before the dive, and at 30 min and 1, 2, 3 and 4 h post-dive, exhaled breath was collected and followed by pulmonary function tests. Exhaled breath samples were analyzed using gas chromatography-mass spectrometry (GC-MS). After univariate tests and correlation of retention times, ion fragments could be identified using a standard reference database (National Institute of Standards and Technology). Using these fragments VOCs could be reconstructed, which were then tested longitudinally with ANOVA. Results:After GC-MS analysis, seven relevant VOCs (generally methyl alkanes) were identified. Decane and decanal showed a significant increase after an oxygen dive (p=0.020 and p=0.013, respectively). The combined intensity of all VOCs showed a significant increase after oxygen diving (p=0.040), which was at its peak (+35%) 3 h post-dive. Diffusion capacity of nitric oxide and alveolar membrane capacity showed a significant reduction after both dives, whereas no other differences in pulmonary function tests were significant. Discussion:This study is the largest analysis of exhaled breath after in water oxygen dives to date and the first to longitudinally measure VOCs. The longitudinal setup showed an increase and subsequent decrease of exhaled components. The VOCs identified suggest that exposure to a one-hour dive with a partial pressure of oxygen of 192.5 kPa damages the phosphatidylcholine membrane in the alveoli, while the spirometry and diffusion capacity show little change. This suggests that exhaled breath analysis is a more accurate method to measure pulmonary oxygen toxicity.